การสังเคราะห์และการหาลักษณะเฉพาะของโครงสร้างนาโนซิงก์ออกไซด์โดยวิธีตกตะกอนโดยตรงเพื่อประยุกต์เป็นเซลล์แสงอาทิตย์ชนิดสีย้อมไวแสง - ศักดา เขื่อนรอบเขต (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
In this work, zinc oxide (ZnO) nanostructures were prepared by direct precipitation method. First, the ZnO precursors were synthesized by reaction of 0.4 M of zinc nitrate hexahydrate (Zn(NO3)2•6H2O) with various ammonium hydrogen carbonate (NH4HCO3) concentration in the range of 0.1251 M. Then, the precursors were calcined at 400C during 1 h to obtain ZnO nanostructures. After that, field emission scanning electron microscopy (FE-SEM), X-ray diffractometry (XRD), UV-vis spectroscopy and Raman spectroscopy were used to investigate morphology, crystallinity, optical properties and structures properties of ZnO nanostructures, respectively. The morphology of ZnO nanostructures exhibited particle– and rod–like morphology with their mean diameter increased from 53 nm to 5 µm by increasing NH4HCO3 concentration. In addition, ZnO nanostructures obtained by using 0.25 M of NH4HCO3 had minimum mean diameter of 53  14 nm suggesting the optimum condition. XRD patterns of the precursors showed the (200), (020), (021), (002) and (510) peaks that corresponds to the diffraction patterns of zinc carbonate hydroxide (Zn5(OH)6(CO3)2; JCPDS, No. 19-1458). After calcinations, XRD patterns showed the (100), (002), (101) and (102) peaks, attributes to the diffraction pattern of ZnO (JCPDS, No. 89-1397). In addition, transmittance value was decreased by increasing NH4HCO3 concentration. However, ZnO nanostructures obtained by using 0.25 M of NH4HCO3 had maximum transmittance of 36.8%, which related to minimum mean diameter. Finally, ZnO nanostructures were used to fabricate dye-sensitized solar cells (DSSCs). It was found that the maximum efficiency of 0.71% was observed for ZnO nanostructures obtained by using 0.25 M of NH4HCO3.